(untitled) - Biddle, William W (New York, 1965)
A brief narrative description of the journal article, document, or resource. The development process in two communities, a mining county in rural Appalachia and a deteriorating neighborhood in a northern industrial city, is presented in case-study form. Concepts and commonly used terms are defined; a process of development is identified that can be used in groups small enough to permit attention to the growth of persons. The individually participative process is then related to the large-scale planning and complexity found in modern metropolitan living. The research design is outlined, and an attempt is made to clarify the relatedness of community development to various academic disciplines and helping professions. A preliminary identity is given the active community developer, who is essential to the process. Finally, appendixes give further information on community development, especially in the United States, and bibliographies list relevant literature in the social sciences and in world-wide community development.
Keywords: Community development,Phát triển cộng đồng